Scarcity brain : fix your craving mindset and rewire your habits to thrive with enough - Easter, Michael (Health and fitness writer) (Rodale, 2023)
"Michael Easter, author of The Comfort Crisis and one of the world's leading experts on behavior change, shows that the problem isn't you. The problem is your scarcity mindset, left over from our ancient ancestors. They had to constantly seek and consume to survive because vital survival tools like food, material goods, information, and power were scarce and hard to find. But with our modern ability to easily fulfill our ancient desire for more, our hardwired "scarcity brain" is now backfiring. And new technology and institutions--from dating and entertainment apps to our food and economic systems--are exploiting our scarcity brain. They're bombarding us with subversive "scarcity cues," subtle triggers that lead us into low-reward cravings that hurt us in the long run. Scarcity cues can be direct and all-encompassing, like a sagging economy. Or they can be subtle and slight, like our neighbor buying a shiny new car"--